USE OF PEDAGOGICAL SITUATIONS ON FOREIGN LANGUAGE CLASSES IN HIGHER EDUCATION - I.S. Zorenko (Academy of Cognitive and Natural Sciences, 2022)
The article studies the notion of "pedagogical situation". It presents the types of pedagogical situations at foreign language lessons.